FRAGTE2: An Enhanced Algorithm to Pre-Select Closely Related Genomes for Bacterial Species Demarcation - Zeng, Jiaqi; Wang, Yuxiao; Wu, Ziyao; Zhou, Yizhuang (Frontiers in Microbiology, 2022)
We previously reported on FRAGTE (hereafter termed FRAGTE1), a promising algorithm for sieving (pre-selecting genome pairs for whole-genome species demarcation). However, the overall amount of pairs sieved by FRAGTE1 is still large, requiring seriously unaffordable computing cost especially for large datasets. Here, we present FRAGTE2. Tests on simulated genomes, real genomes and metagenome-assembled genomes revealed that (i) FRAGTE2 outstandingly reduces ~50-60.10% of overall amount of pairs sieved by FRAGTE1, dramatically decreasing the computing cost required for whole-genome species demarcation afterwards; (ii) FRAGTE2 shows superior sensitivity than FRAGTE1; (iii) FRAGTE2 shows higher specificity than FRAGTE1 and (iv) FRAGTE2 is faster than or comparable with FRAGTE1. Besides, FRAGTE2 is independent of genome completeness, the same as FRAGTE1. We therefore recommend FRAGTE2 tailored for sieving to facilitate species demarcation in prokaryotes.